Development of Gastronomic Tourism Guide Application - Nabilla, Tsara; Turgarini, Dewi; Pratiwi, Ilma Indriasri (Program Studi Pendidikan Pariwisata, Universitas Pendidikan Indonesia, 2022)
The purpose of this research is to identify the needs and desires of gastronomic tourists in Bandung City (to build personalization) to be further compiled as a recommendation for gastronomic tourism in Bandung City which is practical, interactive and advanced by utilizing technology. The method used is research and development. The development procedure refers to the ADDIE (Analysis, Design, Development, Implementation and Evaluations) model. Field data collection used a questionnaire technique which was distributed to 37 gastronomic tourists in Bandung City via Google form. The final result of this research is a gastronomic travel guide mobile application that provides recommendations based on the needs and desires (personalization) of tourists in Bandung City.